Extraskeletal Ewing Sarcoma: Report of an Extremely Rare Case in Temporal Region - Shahryar Bashiri; Hossein Heidar; Milad Parvin (Tehran University of Medical Sciences, 2018)
Extraskeletal Ewing sarcoma (EES) is an uncommon tumor with low prevalence in the head and neck region. Herein, we report a 13-year-old boy with EES in the temporal region, which was managed by surgery and chemotherapy. The histological characteristics and the clinical manifestations of the lesion and our surgical approach will be discussed as well.